A combined attitude and sun tracking system for spacecraft using fuzzy logic control - Chak, Yew Chung (2019)
Many spacecraft attitude control systems today use reaction wheels to deliver precise torques to achieve a three-axis attitude stabilization. Despite the extensive studies in attitude controllers, failures still can occur in a spacecraft system. For example, if a spacecraft suffers multiple reaction wheel failure, external disturbances will cause the spacecraft to tumble and lose its ability to correct the attitude error. If the failure is irrecoverable, it may cause the spacecraft to spin uncontrollably and jeopardize the space mission. The most common way to recover a tumbling spacecraft is by firing chemical thrusters sequentially to generate a torque, which can control the total momentum of the spacecraft. Since the thrusters expel reaction mass to produce a torque, this leads to increased fuel consumption and eventually shortened operational life.